2021
DOI: 10.1073/pnas.2017735118
|View full text |Cite
|
Sign up to set email alerts
|

Fossil dermal denticles reveal the preexploitation baseline of a Caribbean coral reef shark community

Abstract: Preexploitation shark baselines and the history of human impact on coral reef–associated shark communities in the Caribbean are tpoorly understood. We recovered shark dermal denticles from mid-Holocene (∼7 ky ago) and modern reef sediments in Bocas del Toro, Caribbean Panama, to reconstruct an empirical shark baseline before major human impact and to quantify how much the modern shark community in the region had shifted from this historical reference point. We found that denticle accumulation rates, a proxy fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 69 publications
1
17
0
Order By: Relevance
“…However, we note and agree with Naylor et al that there are distinct taxonomic groupings of denticle morphotype diversity, which allows them to be used as broad-scale indicators of elasmobranch evolution (3,4,6). Indeed, taxonomically distinct denticles in reef sediments correlate with the relative abundance and presence of those shark species in the local area (7) and have been used to reconstruct historical shark communities on coral reefs (8).…”
supporting
confidence: 86%
“…However, we note and agree with Naylor et al that there are distinct taxonomic groupings of denticle morphotype diversity, which allows them to be used as broad-scale indicators of elasmobranch evolution (3,4,6). Indeed, taxonomically distinct denticles in reef sediments correlate with the relative abundance and presence of those shark species in the local area (7) and have been used to reconstruct historical shark communities on coral reefs (8).…”
supporting
confidence: 86%
“…Morphological studies classified the dermal denticles into five functional morphotypes: drag reduction, abrasion strength, ridged abrasion strength, generalized functions and defence (Dillon et al , 2017, 2021; Ferrón & Botella, 2017; Raschi & Tabit, 1992; Reif, 1978, 1985). The results showed that L. nasus oral denticles can be classified as abrasion strength as its denticle is diamond‐shaped, lacks lateral cusps and has less pronounced ridges, which are restricted to the anterior portion of the denticle.…”
Section: Discussionmentioning
confidence: 99%
“…According to Dillon et al . (2021), drag reduction and abrasion strength morphotypes are mostly found in pelagic and active sharks such as Carcharhinidae and Sphyrnidae, whereas ridged abrasion strength is observed in demersal sharks such as Ginglymostomatidae. In addition, Reif (1978) classified most Carcharhiniformes as bearing the drag reduction morphotype, e.g., Negaprion , Galeocerdo , Triaenodon , Galeorhinus , Prionace , Sphyrnidae, Carcharhinus spp., and also some Lamniformes such as Alopias vulpinus and members of the family Lamnidae, that is, a morphotype related to active and pelagic life habits.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research on pre-scientific accounts and museum collections has helped identify the presence of 2 sawfish species in the Mediterranean Sea, a region previously deemed to have unsuitable environmental temperatures for these species (Ferretti et al 2016). Dermal denticles from sediment cores allowed reconstruction of pre-human elasmobranch community baselines in coral reef ecosystems (Dillon et al 2017(Dillon et al , 2021.…”
Section: How Can We Reconstruct Elasmobranch Baselines To Inform Popu...mentioning
confidence: 99%